Prevalence of obesity and associated risk factors among university students using the newly developed Student Lifestyle and Obesity Risk Questionnaire (SLORQ): a cross-sectional study - Mohamed K. Seyam (PeerJ)
Background Obesity is a significant global health challenge, with a rising prevalence among young adults. University students are particularly vulnerable to lifestyle transitions and environmental influences. However, current assessment tools lack comprehensive multidimensional coverage of obesity risk factors, especially tailored to the cultural context of Saudi University students, representing a significant gap this study aims to address. Objectives To determine the prevalence of obesity among university students and identify behavioral, environmental, and demographic risk factors contributing to obesity via the Student Lifestyle and Obesity Risk Questionnaire (SLORQ). Methods This cross-sectional study was conducted from March to July 2024 and involved 907 students across 11 colleges at Majmaah University. Anthropometric data (height and weight) were objectively measured by the primary author, with students barefoot and wearing minimal clothing. The participants completed a self-reported validated, bilingual questionnaire (SLORQ) assessing six domains: physical activity, dietary habits, sleep patterns, weight management, metabolic health, and environmental factors. Data were analyzed using descriptive statistics (means, standard deviations), chi-square tests for categorical associations, and multiple linear regression for continuous predictors. Structural validity was assessed via principal component analysis (PCA); reliability included Cronbach’s α (≥ 0.70) and intrarater reliability, intraclass correlation coefficients (ICC). Results Following data collection, statistical analyses revealed that the prevalence of obesity was 15% (n = 136), with 40% classified as overweight. SLORQ scores revealed inverse relationships between body mass index (BMI) and health behaviors, particularly dietary habits (r =  − 0.912, p < 0.001) and physical activity (r =  − 0.614, p < 0.001). No significant differences in BMI were observed based on gender, age, or region. Regression analysis indicated that diet, sleep, and physical activity accounted for most of the variance in BMI, highlighting their importance in obesity prevention. The questionnaire’s internal consistency (Cronbach’s α = 0.915) and intrarater reliability (ICC = 0.999) were assessed to ensure validity. Conclusion Obesity among university students at Majmaah University is influenced by poor dietary practices, inadequate physical activity, and insufficient sleep. These findings underscore the need for targeted health promotion campaigns and campus-wide interventions to address modifiable risk factors. The SLORQ has proven effective in assessing multidimensional obesity risk factors and can guide future research and policymaking.